Prior Experience, Perceived Usefulness and the Web: Factors Influencing Agricultural Audiences’ Adoption of Internet Communication Tools - Tracy Irani (Journal of Applied Communications, 2000)
This study, using the Technology Acceptance Model as a theoretical framework, investigated the effect of prior experience on subjects’ perceptions of perceived usefulness and intent to use Internet communications tools. Results indicated that respondents who had relevant prior experience had the most favorable perceptions of the perceived usefulness of these technologies. Further, those subjects who had high levels of experience and perceived usefulness were most likely to use Internet communications technologies, while those subjects who scored low in both of these areas were least likely. Linear regression analysis indicated that, for all subjects, experience and perceived usefulness were the strongest predictors of behavioral intent to use Internet communications tools.